(untitled) (The Research of Medical Science Review, 2025)
Background: Tuberculosis (TB) and diabetes mellitus (DM) are closely linked, with DM worsening TB severity. However, studies show conflicting findings on DM frequency in TB and its impact on HRCT patterns. No local studies address these variations. Given this controversy, this study was planned to evaluate HRCT findings in diabetic versus non-diabetic TB patients. Objectives: To determine the frequency of diabetes in patients with pulmonary tuberculosis. 2) To compare the high resolution computed tomography findings of pulmonary tuberculosis in diabetic versus non-diabetic patients. Duration: Six months w.e.f 21-12-2023 to 20-06-2024 Methodology: Two hundred pulmonary TB patients were enrolled and referred for HRCT. Demographics, including age, gender, BMI, smoking, and hypertension, were recorded. Patients were categorized into diabetic and non-diabetic groups. HRCT findings were analyzed using SPSS 25.0. The chi-square test assessed differences, with p < 0.05 considered significant. Stratification ensured robust comparisons. Results: Mean age of 53.82 ± 9.07 years; 60.5% were male, and 39.5% were female. The mean BMI was 25.26 ± 3.01 kg/m², with 46.0% having normal weight and 54.0% being overweight or obese. Diabetes was present in 39.5% of cases. HRCT findings showed significantly higher rates of non-segmental consolidation (22.8% vs. 7.4%, p=0.002), multiple cavities (24.1% vs. 5.8%, p < 0.001), and the bud-in-tree sign (30.0% vs. 18.2%, p=0.045) in diabetics. Other findings, including consolidation, nodules, and pleural effusion, were comparable (p > 0.05). Stratification results remained consistent. Conclusion: The study found diabetes in 39.5% of pulmonary tuberculosis patients. Diabetics had significantly higher rates of non-segmental consolidation, multiple cavities, and the bud-in-tree sign on HRCT, while other findings showed no significant differences. Stratification yielded similar results, underscoring diabetes' impact on TB severity and its influence on pulmonary manifestations.